2022
DOI: 10.3390/nu14235157
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Pharmacological Actions of Syringetin and Its Natural Derivatives—A Summary Review

Abstract: Mono- and poly-O-methylated flavonols and their glycoside derivatives belong to the group of natural plant polyphenols with a wide spectrum of pharmacological activities. These compounds are known for their antioxidant, antimutagenic, hepatoprotective, antidiabetic, and antilipogenic properties. Additionally, they inhibit carcinogenesis and cancer development. Having in mind the multidirectional biological activity of methylated flavonols, we would like to support further study on their health-promoting activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…It is also able to inhibit the growth of cancer cells via the induction of cell cycle arrest in the G2/M phase and the initiation of apoptosis. Syringetin can inhibit the alpha-glucosidase enzyme, so it can reduce postprandial glycemia [122].…”
Section: Minimum Inhibitory Concentration (Mic) Of Fungal Extractsmentioning
confidence: 99%
“…It is also able to inhibit the growth of cancer cells via the induction of cell cycle arrest in the G2/M phase and the initiation of apoptosis. Syringetin can inhibit the alpha-glucosidase enzyme, so it can reduce postprandial glycemia [122].…”
Section: Minimum Inhibitory Concentration (Mic) Of Fungal Extractsmentioning
confidence: 99%
“…Syringaldehyde, a naturally occurring compound found in a wide range of plants, has been extensively studied for its diverse biological activities. Its derivatives have been shown to possess various beneficial properties, including anti-inflammatory, anticancer, and potent antioxidant activities [11][12][13]. As a result, the search for antioxidant compounds has expanded to various fields of research, including nutrition, pharmacology, and biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…As well as cardiovascular disease, it is also used in the treatment of anemia trouble and rheumatism. [10] Recent studies reported antioxidant, [15][16][17][18] Antiinflammatory, [19] Antimicrobial [20,21] , hypoglycemic, [22,23] Hepatoprotective, [24] anti-Alzheimer, [25,26] antidiabetic [9,27] and Wound healing [15] properties of plant extracts and phytochemicals from Mediterranean saltbush.…”
Section: Introductionmentioning
confidence: 99%